IMPLEMENTATION OF BASKET MKING SKILLS LIDI THROUGH PROCESS SKILLS APPROACH FOR DEAF CHILDREN CLASS IV (SLB Classroom Action Research on Mother Love New Market Painan) - Irefridayeni - Irefridayeni (Jurnal Penelitian Pendidikan Khusus, 2013)
The background of this research is the discovery of three fourth grade deaf students who havedifficulty in making a rib basket, when following the subjects were given the skills of teachers, it is because the classroom teacher can not perform deliver the subject matter inaccordance with the steps of learning to make baskets stick, and so far only using the demonstration teacher in providing skills subjects, thus making students often forget or become less understand what the teacher explained. In other circumstances at the time of making baskets stick when children have difficulty forming rib weave baskets. The purpose of this research is to improve the ability to make baskets stick through process skills approach for children with hearing impairment grade IV. This research is action research (classroom action research), takes the form of collaboration with colleagues. These actions were taken three deaf children in the fourth grade SLB Mother Love New Market Painan. The results during the first cycle held four meetings in the learning process that starts from preparing the tools, sharpening a stick, give color, weaving, and assessment of the work of children. Based on the average value obtained by the students at the end of the cycle I can see that Ro before the given action I get a value of 40% of all the indicators are given. And after a given action I got 60%. While Nd before the given action I got 30% of all the indicators are given. After the action I was given to 50%. And Yp before the given action I get a value of 40% of all the indicators were given, and after being given the action I got 50%. In the second cycle performed in the four skills of learning to make baskets sticks, where Ro got a score of 70% on the implementation of the second cycle, Nd got 60%, and 70% Yp get value. From the results presentation and analysis of the data it can be concluded that the use of process skills approach can improve stick skills make baskets for deaf children in the fourth grade SLB Mother Love New Market Painan. Thus it can be suggested to the schools, teachers, and researchers can use the following to process skills in improving learning skills for other children.